Mixed Valency vs Radical Bridge Formulation in Symmetrically and Asymmetrically Ligated Diruthenium Complexes - Mondal, Sudipta; Schwederski, Brigitte; Záliš, Stanislav; Kaim, Wolfgang (European journal of inorganic chemistry, 2022)
The asymmetrical dinuclear [{(trpy*)Ru}2(μ‐adc‐Salph)Cl](PF6) 1(PF6), trpy*=4,4’,4”‐tri‐tert‐butyl‐2,6,2’,6”‐terpyridine, adc‐Salph=1‐benzoyl‐2‐salicyloylhydrazido(3‐), and the related symmetrical dinuclear [{Cl(trpy*)Ru}2(μ,η2 : η2‐adc‐Ph)](PF6) 2(PF6), adc‐Ph=1,2‐bis(benzoyl)hydrazido(2‐), were synthesized and structurally characterized. Both paramagnetic compounds were compared with the previously reported symmetrical [{(trpy*)Ru}2(μ,η3 : η3‐adc‐Sal)](PF6) 3(PF6) containing the bis‐tridentate bridge 1,2‐bis(salicyloyl)hydrazido(4‐). Molecular structures and magnetic resonance features (1H NMR, EPR) indicate spin density distribution over the metal(s) and the bridging ligand. Reversible one‐electron reduction and oxidation were possible in all instances yielding comproportionation constants Kc of about 109 for the paramagnetic intermediates 1+–3+. Structural results, spin density distribution and UV‐Vis‐NIR spectroelectrochemistry were analyzed for 1+ with the help of TD‐DFT calculations for a model compound (tert‐Bu→Me). Intense absorptions around λmax=1450–1650 nm for the cations were assigned to mixed metal/ligand transitions with significant inter‐valence charge transfer (IVCT) character. For both the symmetrical and asymmetrical arrangements the cationic intermediates can be described as considerably mixed metal/ligand systems. A comparative study of three related diruthenium complex redox systems reveals notably small effects from asymmetry in 1(PF6) as compared to symmetrical analogues. Electrochemical comproportionation constants, EPR data and near IR absorbance of the intermediates do not reflect the asymmetry in spite of the slanted spin distribution.